Studi Optimasi Pemanfaatan Air Irigasi Menggunakan Program Linier pada Daerah Irigasi Pirang Kabupaten Bojonegoro - Triwidianto, Heru; Limantara, Lily Montarcih; Soetopo, Widandi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2023)
The Pirang Irrigation Area has a total area of 1,314 hectares of raw rice fields located in Bojonegoro Regency. The problems that occur in this irrigation area are irregularities in the implementation of cropping pattern that are not according to the plan and the availability of water that cannot meet irrigation needs. Therefore, it is necessary to optimize the available land area and discharge to maximize agricultural profits. Optimization is carried out using a linear programming method with a solver facility in Microsoft Excel. In this study, 1 existing cropping pattern and 4 alternative are planned with 80% and 50% mainstay discharge conditions. The results of the water balance at each cropping pattern before being optimized experienced a water balance deficit with a percentage of 22-25%. However, after optimizing all cropping patterns, none of them experienced a water balance deficit. The optimization results also showed that each alternative cropping pattern experienced an increase in planting intensity and also the benefits of agricultural products compared to the existing cropping pattern at 80% and 50% mainstay discharge conditions. For the best cropping pattern at 80% mainstay discharge conditions, namely alternative 3 (rice Â- peanut - rice) with a planting intensity of 228.33% and a profit of Rp. 54,664,759,359, and in the 50% mainstay discharge condition, alternative 1 was chosen (rice, corn - rice, corn - rice, corn) with a planting intensity of 253.37% and a profit of Rp. 54,099,646,076.Â Daerah Irigasi Pirang memiliki luas baku sawah 1.314 Ha yang berlokasi di Kabupatern Bojonegoro. Permasalahan yang terjadi pada daerah irigasi ini yaitu penyimpangan pelaksanaan PTT yang tidak sesuai rencana serta ketersediaan air yang tidak dapat mencukupi kebutuhan irigasi. Maka dari itu diperlukanlah pengoptimalan luas lahan dan debit yang tersedia sehingga dapat memaksimalkan keuntungan pertanian. Optimasi dilakukan menggunakan metode program linier dengan alat bantu fasilitas solver pada Microsoft Excel. Pada studi ini direncanakan 1 PTT eksisting dan 4 PTT alternatif dengan kondisi debit andalan 80% dan 50%. Hasil neraca air pada setiap PTT sebelum dioptimasi mengalami defisit neraca air dengan persentase 22-25%. Namun, setelah dioptimasi seluruh PTT tidak ada yang mengalami defisit neraca air. Dari hasil optimasi juga menunjukkan pada setiap PTT alternatif mengalami peningkatan intensitas tanam dan juga keuntungan hasil pertanian daripada PTT eksisting di kondisi debit andalan 80% maupun 50%. Untuk PTT terbaik pada kondisi debit andalan 80% yaitu alternatif 3 (padi - palawija (kacang tanah) - padi) dengan intensitas tanam 228,33% dan keuntungan Rp. 54.664.759.359, serta pada kondisi debit andalan 50% terpilih alternatif 1 (padi, palawija (jagung) - padi, palawija (jagung) - padi, palawija (jagung)) dengan intensitas tanam 253,37% dan keuntungan Rp. 54.099.646.076.